Predicting rehabilitation length of stay in Canada: It's not just about impairment. (2nd November 2017) - Catharine Craven, B.; Kurban, Dilnur; Farahani, Farnoosh; Rivers, Carly S.; Ho, Chester; Linassi, A. Gary; Gagnon, Dany H.; O'Connell, Colleen; Ethans, Karen; Bouyer, Laurent J.; Noonan, Vanessa K.; ,
Abstract : Introduction: Current tertiary Spinal Cord Injury (SCI) rehabilitation funding and rehabilitation length of stay (R-LOS) in most North American jurisdictions are linked to an individual's impairment. Our objectives were to: 1) describe the impact of relevant demographic, impairment and medical complexity variables at rehabilitation admission on R-LOS among adult Canadians with traumatic SCI; and 2) identify factors which extend R-LOS. Methods: Data from 1, 376 adults with traumatic SCI were obtained via chart abstraction and administrative data linkage from 15 Rick Hansen SCI Registry sites (2004–2014). Variables included age, sex, neurological impairment (level, severity), rehabilitation onset days, R-LOS, Glasgow Coma Score (GCS) at admission, prior ventilation or endotracheal tube (Vent/ETT), or indwelling bladder catheter at acute discharge, pain interference score, intensive care unit (ICU) length of stay (LOS), and lower extremity motor scores (LEMS) at rehabilitation admission. Variables related to R-LOS in bivariate analysis were included in multivariate analysis to determine their impact on R-LOS. Results: Prior Vent/ETT tube, indwelling bladder catheter, GCS, LEMS, and neurological impairment were related to R-LOS in bivariate analysis. Multivariate linear regression analyses identified five variables as significant predictors: age, Vent/ETT for >24 hours in acute care, indwelling bladder catheter at acute discharge, LEMS, and NLI/AIS subgroup at rehabilitation admission explained 32% of the variation in R-LOS (p<0.001). Conclusions: Based on the enclosed formula, and knowledge of an individual's age at injury, spinal cord impairment (level and severity), prior Vent/ETT, presence of an indwelling bladder catheter, and LEMS at admission, administrators and clinicians may readily identify patients for whom an extended R-LOS beyond conventional LOS targets is likely.